Peripheral immune characteristics and subset disorder in reproductive females with endometriosis - Lin, Kai-Rong; Li, Pei-Xian; Zhu, Xiao-hong; Mao, Xiao-fan; Peng, Jia-Li; Chen, Xiang-Ping; SiTu, Cui-Yao; Zhang, Li-Fang; Luo, Wei; Han, Yu-Bin; Yu, Si-Fei (Frontiers in Immunology, 2024)
Pathogenesis of endometriosis (EN) is still unknown, but growing evidence suggests that immune regulation may be important, and the pattern of peripheral immune changes in reproductive women with EN has yet to be fully explored. In this study, we conducted a comprehensive and systematic analysis of immune cell subsets within T cells, B cells, NK cells, and γδ T cells in peripheral blood (PB) samples from women with EN, women with uterine fibroids (UF) but without EN (UF-alone), and healthy controls using multi-parameter flow cytometry. Our findings revealed that UF, a common comorbidity of EN, exhibited similar peripheral immune features to EN, particularly in T cell and B cell immunity. Compared to healthy controls, we constructed the peripheral immune profile of EN. This profile highlighted that the immunopathogenic factors in EN predominantly relate to the immune disorder of B cells and their subsets, as well as the functional abnormalities within immune cell subsets of CD4+ T cells, CD8+ T cells, and γδ T cells. Moreover, using the random forest (RF) machine-learning method, we developed a diagnostic model that can effectively identify the patients with EN from healthy controls. The immune factors identified within this model could be pivotal for unraveling the immune pathogenic mechanisms of EN. Our study is the first to present a comprehensive depiction of the circulating immune features in EN, although the detailed roles and underlying mechanisms of these immune factors in the context of EN require further investigation.